Intraoperative drug delivery to hindbrain tumours via an injectable hydrogel is well tolerated and confers survival benefit against atypical teratoid/rhabdoid xenografts - Cara Moloney; Phoebe McCrorie; Amr ElSherbeny; Harry Porter; Chiara Bastiancich; Hasan Slika; Aanya Shahani; Emre Derin; Esteban Velarde; Jackson Miller; John Theodore; Khushi Varshney; et al. (Drug Delivery and Translational Research, 2026)

Linkage Between Sex Ratio and Sea Age Composition of Atlantic Salmon in Scottish Rivers - Stuart J. Middlemas; James N. Sampayo; Jason I. Henry; Yee Mai Bradley; Nora N. Hanson (Fisheries Management and Ecology, 2026)

Camizestrant-induced heart rate reduction is mediated via a sinoatrial node pacemaker channel mechanism - Andrew Hall; Saïd El-Haou; Inmaculada C. Villar; David Molla; Maggie Kwan; Stuart Purbrick; David Henry; Jason Kirk; Glen Hawthorne; Serena Canzolino; Joanna Harding; Alexander Harmer; et al. (Toxicology and Applied Pharmacology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Modelling the response of common carp (Cyprinus carpio) to natural and managed flows using a stochastic population model - Charles R. Todd; John D. Koehn; Ivor G. Stuart; Henry F. Wootton; Brenton P. Zampatti; Leigh Thwaites; Anthony Conallin; Qifeng Ye; Kasey Stamation; Chris Bice (Biological Invasions, 2024)

Modelling the probability of meeting IUCN Red List criteria to support reassessments - Etienne G. Henry; Luca Santini; Stuart H. M. Butchart; Manuela González‐Suárez; Pablo M. Lucas; Ana Benítez‐López; Giordano Mancini; Martin Jung; Pedro Cardoso; Alexander Zizka; Carsten Meyer; H. Reşit Akçakaya; et al. (Global Change Biology, 2024)
Comparative extinction risk analysis—which predicts species extinction risk from correlation with traits or geographical characteristics—has gained research attention as a promising tool to support extinction risk assessment in the IUCN Red List of Threatened Species. However, its uptake has been very limited so far, possibly because existing models only predict a species' Red List category, without indicating which Red List criteria may be triggered. This prevents such approaches to be integrated into Red List assessments. We overcome this implementation gap by developing models that predict the probability of species meeting individual Red List criteria. Using data on the world's birds, we evaluated the predictive performance of our criterion‐specific models and compared it with the typical criterion‐blind modelling approach. We compiled data on biological traits (e.g. range size, clutch size) and external drivers (e.g. change in canopy cover) often associated with extinction risk. For each specific criterion, we modelled the relationship between extinction risk predictors and species' Red List category under that criterion using ordinal regression models. We found criterion‐specific models were better at identifying threatened species compared to a criterion‐blind model (higher sensitivity), but less good at identifying not threatened species (lower specificity). As expected, different covariates were important for predicting extinction risk under different criteria. Change in annual temperature was important for criteria related to population trends, while high forest dependency was important for criteria related to restricted area of occupancy or small population size. Our criteria‐specific method can support Red List assessors by producing outputs that identify species likely to meet specific criteria, and which are the most important predictors. These species can then be prioritised for re‐evaluation. We expect this new approach to increase the uptake of extinction risk models in Red List assessments, bridging a long‐standing research‐implementation gap.

Compactive deformation of incoming calcareous pelagic sediments, northern Hikurangi subduction margin, New Zealand: Implications for subduction processes - Maomao Wang; Philip M. Barnes; Julia K. Morgan; Rebecca E. Bell; Gregory F. Moore; Ming Wang; Ake Fagereng; Heather Savage; Davide Gamboa; Robert N. Harris; Stuart Henrys; Joshu Mountjoy; et al. (Earth and Planetary Science Letters, 2023)

Coastal freshening drives acidification state in Greenland fjords - Henry C. Henson; Johnna M. Holding; Lorenz Meire; Søren Rysgaard; Colin A. Stedmon; Alice Stuart-Lee; Jørgen Bendtsen; Mikael Sejr (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: TCA cycle metabolic compromise due to an aberrant S‑nitrosoproteome in HIV‑associated neurocognitive disorder with methamphetamine use - Paschalis‑Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

TCA cycle metabolic compromise due to an aberrant S-nitrosoproteome in HIV-associated neurocognitive disorder with methamphetamine use - Paschalis-Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

Rapid decreases in relative testes mass among monogamous birds but not in other vertebrates - Joanna Baker; Stuart Humphries; Henry Ferguson‐Gow; Andrew Meade; Chris Venditti (Ecology Letters, 2020)
Larger testes produce more sperm and therefore improve reproductive success in the face of sperm competition. Adaptation to social mating systems with relatively high and low sperm competition are therefore likely to have driven changes in relative testes size in opposing directions. Here, we combine the largest vertebrate testes mass dataset ever collected with phylogenetic approaches for measuring rates of morphological evolution to provide the first quantitative evidence for how relative testes mass has changed over time. We detect explosive radiations of testes mass diversity distributed throughout the vertebrate tree of life: bursts of rapid change have been frequent during vertebrate evolutionary history. In socially monogamous birds, there have been repeated rapid reductions in relative testes mass. We see no such pattern in other monogamous vertebrates; the prevalence of monogamy in birds may have increased opportunities for investment in alternative behaviours and physiologies allowing reduced investment in expensive testes.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Author Correction to: Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Sleeper cells: the stringent response and persistence in the Borreliella ( Borrelia ) burgdorferi enzootic cycle - Felipe C. Cabello; Henry P. Godfrey; Julia V. Bugrysheva; Stuart A. Newman (Environmental Microbiology, 2017)
Summary Infections with tick‐transmitted Borreliella ( Borrelia ) burgdorferi , the cause of Lyme disease, represent an increasingly large public health problem in North America and Europe. The ability of these spirochetes to maintain themselves for extended periods of time in their tick vectors and vertebrate reservoirs is crucial for continuance of the enzootic cycle as well as for the increasing exposure of humans to them. The stringent response mediated by the alarmone (p)ppGpp has been determined to be a master regulator in B . burgdorferi . It modulates the expression of identified and unidentified open reading frames needed to deal with and overcome the many nutritional stresses and other challenges faced by the spirochete in ticks and animal reservoirs. The metabolic and morphologic changes resulting from activation of the stringent response in B . burgdorferi may also be involved in the recently described non‐genetic phenotypic phenomenon of tolerance to otherwise lethal doses of antimicrobials and to other antimicrobial activities. It may thus constitute a linchpin in multiple aspects of infections with Lyme disease borrelia, providing a link between the micro‐ecological challenges of its enzootic life‐cycle and long‐term residence in the tissues of its animal reservoirs, with the evolutionary side effect of potential persistence in incidental human hosts.

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Erratum to: Indigenous frameworks for observing and responding to climate change in Alaska - Patricia Cochran; Orville H. Huntington; Caleb Pungowiyi; Stanley Tom; F. Stuart Chapin; Henry P. Huntington; Nancy G. Maynard; Sarah F. Trainor (Climatic Change, 2014)

Indigenous frameworks for observing and responding to climate change in Alaska - Patricia Cochran; Orville H. Huntington; Caleb Pungowiyi; Stanley Tom; F. Stuart Chapin; Henry P. Huntington; Nancy G. Maynard; Sarah F. Trainor (Climatic Change, 2013)

The potential influence of shallow gas and gas hydrates on sea floor erosion of Rock Garden, an uplifted ridge offshore of New Zealand - Gareth J. Crutchley; Sebastian Geiger; Ingo A. Pecher; Andrew R. Gorman; Hai Zhu; Stuart A. Henrys (Geo-Marine Letters, 2010)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

A kinetic mechanism for nicotinic acetylcholine receptors based on multiple allosteric transitions - Stuart J. Edelstein; Olivier Schaad; Eric Henry; Daniel Bertrand; Jean-Pierre Changeux (Biological Cybernetics, 1996)